Synthesis, characterization, x-ray structure, DNA cleavage, and cytotoxic activities of palladium(ii) complexes of 4-phenyl-3-thiosemicarbazide and triphenylphosphane - Rocha, Fillipe Vieira [UNESP]; Barra, Carolina Valério [UNESP]; Mauro, Antonio Eduardo [UNESP]; Carlos, Iracilda Z. [UNESP]; Nauton, Lionel; El Ghozzi, Malika; Gautier, Arnaud; Morel, Laurent; Netto, Adelino Vieira de Godoy [UNESP] (Wiley, 2013)
Complexes of the type [PdX(PPh3)(1)]X [1 = 4-phenyl-3- thiosemicarbazide; X = Cl- (2), Br- (3), I- (4), and SCN- (5)] have been synthesized and characterized by elemental analyses and IR, UV/Vis, and 1H and 13C NMR spectroscopy. The molecular structure of complex 4 was determined by single-crystal X-ray diffraction. The binding of the complexes with a purine base (guanosine) was investigated by 1H NMR spectroscopy and mass spectrometry, which showed the complexes to coordinate to guanosine through N7. A gel electrophoresis assay demonstrated the ability of 2-5 to cleave DNA plasmid. All the complexes were tested in vitro by means of the MTT assay for their cytotoxicity against two murine cell lines, LM3 (mammary adenocarcinoma) and LP07 (lung adenocarcinoma), and compared with cisplatin. Complexes 2-5 exhibited good cytotoxicity that surpasses that of cisplatin in the case of LM3. A series of thiosemicarbazide/phosphane palladium(II) complexes have been synthesized and fully characterized. These complexes are able to cleave DNA plasmid and show cytotoxicity against adenocarcinoma (mammary LM3 and lung LP07), surpassing the cytotoxicity of cisplatin in the case of LM3. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Antitumor agents; Biological activity; DNA cleavage; Palladium